Initial Reports of the Deep Sea Drilling Project 1987
DOI: 10.2973/dsdp.proc.88.108.1987
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Source Seismic Experiment at Hole 581C

Abstract: Seismic refraction lines fired to ocean bottom seismometers (OBS) and to the ocean sub-bottom seismometer (OSS) at Site 581 provide some of the highest quality refraction data yet obtained in the deep ocean. A particularly useful subset of these data had a Soviet air gun as a source and an OBS as a receiver. Excellent data with a shot spacing of less than 250 m are well recorded out to a range of 45 km. These data are analyzed with WKBJ, r-p inversion, and reflectivity modeling which are used to obtain seismic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Low-velocity zones in the lower oceanic crust have been proposed by many workers (e.g. Lewis, 1978;Lewis and Snydsman (1979);Duennebier et al, 1987), and are often interpreted in terms of the alteration of olivinerich mafic and ultramafic rocks to serpentine (e.g. Lewis, 1978).…”
Section: Implications For Crustal Structurementioning
confidence: 99%
“…Low-velocity zones in the lower oceanic crust have been proposed by many workers (e.g. Lewis, 1978;Lewis and Snydsman (1979);Duennebier et al, 1987), and are often interpreted in terms of the alteration of olivinerich mafic and ultramafic rocks to serpentine (e.g. Lewis, 1978).…”
Section: Implications For Crustal Structurementioning
confidence: 99%
“…Since Houtz and Ewing [1976] first documented an age-dependent increase in the velocity of the uppermost crust, several studies have confirmed this relationship. In the Pacific alone, these studies include conventional refraction [Spudich and Orcutt, 1980;Purdy, 1982;Bratt and Purdy, 1984;Bratt and Solomon, 1984;McClain and Atallah, 1985;Bee and Bibee, 1989;, borehole [Stephen and Harding, 1983;Little and Stephen, 1985;Duennebier et al, 1987;Whitmarsh et al, 1987;Collins et al, 1989], single-ship Tolstoy et al, 1997] and two-ship multichannel [Harding et ai., 1989;Vera et ai., 1990], and on-bottom seismics [Christeson et ai., 1994a]. Sensitivity to velocities immediately beneath the seafloor varies between methods.…”
Section: Aging Of Extrusive Crustmentioning
confidence: 99%
“…Our objective was to model the PolSo signal recorded from an earthquake during the OSSIV seismic experiment. The details of this seismic experiment have been reported elsewhere (see Duennebier et al 1987; but are briefly summarized here for completeness.…”
Section: Modelling Of P O L S O D a T A Recorded At O S S I Vmentioning
confidence: 99%
“…Recently, Mallick & Frazer (1986 showed how reflectivity codes can be made to vectorize even when the seismic velocities are frequency dependent. Applications of their method to the modelling of marine seismic refraction data were given in Duennebier & Mallick (1985), Duennebier et al (1987), andSen et al (1988). In this paper their method is used to synthesize Polso seismograms for a variety of oceanic models for comparison with PolSo data recorded during the OSS IV experiment .…”
mentioning
confidence: 99%